The Effect of Contextual Teaching and Learning (CTL) Model on Civics Learning Outcomes of Elementary School Students - Najib, Muhammad (Fakultas Tarbiyah dan Ilmu Keguruan Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2023)
The purpose of this study was to find out whether there was an effect of the learning model on student learning outcomes in Civics class IV SD Negeri 4 Metro Barat. This type of research is a quantitative pre-experimental one-group pretest-posttest type. Pre-experimental type of one-group pretest-posttest is a study that has two tests, namely pretest and pretest. Data collection tools used in this research are observation, tests, and documentation. Based on the results of the n-gain test as many as 6 students or 46% of students experienced an increase in Civics learning outcomes in the high category, 3 students or 23% of students experienced an increase in the medium category, 1 student or 8% of students experienced an increase in the low category, and 3 students or 23% experienced an increase in the fixed category. The average value of n-gain was obtained at 0.6, which means that the increase in Civics learning outcomes has increased to the moderate category. It can be concluded that in this study the CTL model had an influence on the learning outcomes of Civics in class IV SD Negeri 4 Metro Barat.